Strategi Pemasaran Digital Dalam Meningkatkan Revenue E-Bisnis Live Streaming di Shopee - Zahara, Nabila; Atika, Nanda Nurul; Pitaloka, Sekar Widyamada; Lubis, Syavina Nadhira; N, Nurbaiti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to analyze whether the marketing strategy with the live streaming feature is effective for revenue at Shopee. This research uses descriptive qualitative research methods, which focus on collecting and analyzing data in words to understand the phenomenon being studied. Based on the results of research using the literature review method that has been carried out, it can be concluded that Shopee's digital marketing strategy, using the live streaming feature (Shopee Live), has a positive effect on increasing e-business revenue. With changes in consumer behavior shifting from traditional to online shopping, Shopee utilizes the Shopee Live feature to create direct interactions between sellers and buyers. This interaction introduces products in real-time and provides a more engaging shopping experience. Utilizing digital marketing allows Shopee to understand consumer preferences and tailor marketing content effectively. The research results show that this effective and responsive marketing strategy has succeeded in increasing purchasing decisions for potential consumers which can increase e-business revenue.